HPR1000 pressurizer degassing system design and analysis - Cui, Huaiming; Cai, Zhiyun (Frontiers in Energy Research, 2024)
In HUALONG-1 Unit (HPR1000), the hydrogen (H2) concentration should be reduced to 15 ml(STP)/kg 24 hours before reactor shutdown when Reactor Vessel is scheduled to be opened. Traditional degassing method by letting down the reactor coolant through Chemical and Volume Control System will take longer time and its operation is more complicated. To shorten the degassing time and simplify the operation, this paper proposes a pressurizer degassing system design for HPR1000 by applying the pressurizer as a thermal degassing equipment. Then, the degassing system optimization analysis is carried out under full range of steady operating conditions during shutdown, and the optimal size of the flow limiting orifice plate is obtained.Meanwhile, in order to verify the transient characteristic during the entire degassing process to ensure the operating safety, a dedicated transient degassing program based on an improved non-equilibrium multi-region pressurizer model and a transient degassing model is used then to carry out a transient simulation analysis on this process.The transient simulation results show that, under bounding condition of hot-zero power operation, during the entire degassing process, the pressurizer's pressure drops by a maximum of 0.038 MPa, and the water level rises by 0.016 m above the normal level. As can be seen, both of the pressure and water level are within the normal operation band and shall not initiate any safety signal. Meanwhile, the entire transient process lasts about 24 minutes, and then enters into a stable degassing period. It takes about 5.2 hours to remove the gas dissolved in Reactor Coolant from 35 ml(STP)/kg to 15 ml(STP)/kg. The analysis shows the pressurizer degassing system designed for HPR1000 is safe, effective and reliable.